Pengembangan E-Learning Interaktif untuk Mata Kuliah Komputasi Paralel dan Terdistribusi - Zulkipli, Zulkipli; Mujamil, Ahmad; Alfian, Khaerul; Sutrisno, Shendy Emilia Putri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to enhance students' understanding and engagement through the development of interactive e-learning materials based on Moodle in the course of Parallel and Distributed Computing. The research employs the Research and Development (R&D) method with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The final product of this research consists of a digital module, interactive videos, threading simulations, and assessment instruments. A limited trial involving 30 students showed that the use of interactive media can improve learning outcomes by 28%. Validation by experts places the media's feasibility level in the very valid category with a score of 92%. Through the presentation of interactive and visual materials, this media is considered effective in helping students understand complex concepts. Therefore, this research concludes that interactive e-learning is a potential and effective learning tool to support learning in technical and challenging subjects